2021
DOI: 10.1089/ham.2020.0127
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor-Mediated Excitotoxicity Is Involved in Neuronal Apoptosis and Cognitive Impairment Induced by Chronic Hypobaric Hypoxia Exposure at High Altitude

Abstract: Ji, Weizhong, Yaqing Zhang, Ri-li Ge, Yaqi Wan, and Jie Liu. NMDA receptor-mediated excitotoxicity is involved in neuronal apoptosis and cognitive impairment induced by chronic hypobaric hypoxia exposure at high altitude. High Alt Med Biol. 22:45-57, 2021. Aim: Exposure to chronic hypobaric hypoxia at high altitude can lead to cognitive impairment; however, its underlying mechanism is still unclear. Excessive expression of glutamate and its receptors can induce excitotoxicity and cause neuronal necrosis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Notably, chronic exposure to a hypobaric hypoxia environment at high altitudes (Denver: ∼26 in barometer; ∼17% O 2 ) can lead to neurodegeneration of the hippocampus and prefrontal cortex, which is associated with cognitive impairment. [ 11 ] The act of choosing between heroin versus natural rewards is a cognitive act, and indeed, our data suggests that opioid choice is a distinct measure of OUD compared to other, motivational measures. This led us to dub our heroin choosers “mile high rats.” Interestingly, there are numerous reports on the importance of altitude in anesthesia, including opioid analgesics.…”
mentioning
confidence: 75%
“…Notably, chronic exposure to a hypobaric hypoxia environment at high altitudes (Denver: ∼26 in barometer; ∼17% O 2 ) can lead to neurodegeneration of the hippocampus and prefrontal cortex, which is associated with cognitive impairment. [ 11 ] The act of choosing between heroin versus natural rewards is a cognitive act, and indeed, our data suggests that opioid choice is a distinct measure of OUD compared to other, motivational measures. This led us to dub our heroin choosers “mile high rats.” Interestingly, there are numerous reports on the importance of altitude in anesthesia, including opioid analgesics.…”
mentioning
confidence: 75%
“…In an ALS mouse model, experimentally induced chronic intermittent hypoxia resulted in accelerated motor neuron death and cognitive dysfunction (9). Chronic intermittent hypoxia has also been associated with NMDA-induced excitotoxicity and neuronal apoptosis promoted by upregulated p38MAPK expression (21)(22)(23), both of which have been implicated in ALS pathogenesis (24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increase in hypoxic exposure causes an increase in FRs and oxidative stress, which leads to cognitive impairment and neuronal apoptosis in the hippocampus and cortex. The increase in hypoxic conditions at high altitudes causes an increase in the expression of NMDA and AMPA receptors (Ji et al 2020). Likewise, Mesole et al (2020) demonstrated that aluminum chloride exposure in Wistar rats increased the expression of nitric oxide and 8-hydroxy-2-deoxyguanosine (8-OHdG).…”
Section: Apoptosis and Autophagymentioning
confidence: 98%